The Ineffectiveness of Manual Treatment of Swimming Pools - Chidozie Charles Nnaji; Agina Ifeyinwa; Iloanya Ifeoma (Journal of Applied Sciences and Environmental Management)
The University of Nigeria, Nsukka swimming pool was monitored for a period spanning about three months. The pool was constructed in 1961 and has been in operation since then except that many facilities including the treatment system are no longer functional forcing management to resort to treatment of the pool water by spraying the chemicals on the surface of the water and allowing swimmers to do the mixing. Prior to the physicochemical and microbial monitoring, questionnaires were administered to the swimmers which revealed that there was a level of dissatisfaction among the swimmers. Some of the swimmers were suffering from one form of skin disease or the other, some others had body itch after swimming while some others complained of foul odour. Water samples were collected from the swimming pool and analyzed, and the results were matched against swimming pool water standards. This comparison showed that the swimming pool water does not meet laid down standards as a result of poor management, infrequent treatment due to a permanent breakdown of treatment facilities, and general neglect of the swimming pool. Residual chlorine was detected only twice throughout the monitoring period, the COD was above 80mg/l, the pH was between 6.2 and 7.1 as against 7.2 to 7.8 recommended by standards. The total plate count was within limits but E-coli and coliform were detected in the pool more often than not as against the standard that recommends that E-coli or coliform should not be found in 100ml of the water sample. @JASEM